PENINGKATAN PRODUKTIVITAS DI PT MAZZONI JAVA UTAMA MELALUI IMPLEMENTASI SISTEM INFORMASI DAN KOMUNIKASI - Nur Indah, Mega; Maulidina, Nurbaiti; Evi Yuliana, Margaretha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The development of science and technology has changed the business landscape, forcing companies like PT Mazzoni Java Utama to continue to innovate. PT Mazzoni Java Utama, a manufacturer of sauces and condiments, has been relying on information and communication systems in its operations, although it still uses local systems that are not integrated. In an effort to increase productivity and efficiency, this company needs to adopt a centralized and integrated approach by integrating information and communication technology. This research uses a qualitative method with direct observation as the main approach. With the implementation of more advanced information and communication systems, it is expected that this project will result in significant improvements in productivity, operational cost savings, and reinforcing PT Mazzoni Java Utama's position in an increasingly competitive market. Better alignment between departments within the company, improved workflow, and faster decision-making capabilities are expected to be the positive impacts of this project. Thus, PT Mazzoni Java Utama is ready to face the challenges in the ever-changing and evolving business world.